2019
DOI: 10.1186/s13007-019-0512-y
|View full text |Cite
|
Sign up to set email alerts
|

A simple and rapid protocol for the genetic transformation of Ensete ventricosum

Abstract: Enset (Ensete ventricosum), also known as Ethiopian banana, is a food security crop for more than 20 million people in Ethiopia. As conventional breeding of enset is very challenging, genetic engineering is an alternative option to introduce important traits such as enhanced disease resistance and nutritional value. Genetic transformation and subsequent regeneration of transgenic enset has never been reported mainly due to challenges in developing transformation protocols for this tropical species. Agrobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Purified DNA was digested with EcoR V and fractionated on 1.0% agarose gel. The DNA bands were then transferred onto a nylon membrane (Amersham, USA) by upward capillary in a 20× SSC buffer as previously described [ 72 , 73 ]. The HPT DNA was adopted as a probe, and it was prepared from Hind III restricted fragment of pYL-RNAi (Clontech) and labeled with digoxigenin.…”
Section: Methodsmentioning
confidence: 99%
“…Purified DNA was digested with EcoR V and fractionated on 1.0% agarose gel. The DNA bands were then transferred onto a nylon membrane (Amersham, USA) by upward capillary in a 20× SSC buffer as previously described [ 72 , 73 ]. The HPT DNA was adopted as a probe, and it was prepared from Hind III restricted fragment of pYL-RNAi (Clontech) and labeled with digoxigenin.…”
Section: Methodsmentioning
confidence: 99%
“…Two important aspects of banana molecular breeding are efficient regeneration and genetic transformation ( May et al, 1995 ). In vitro banana cultures have been developed using various explants, such as shoot tips ( Matheka et al, 2019 ), immature male flowers ( Jalil et al, 2003 ), apical meristems ( Novak et al, 1989 ), corms ( May et al, 1995 ), floral apices ( Liu et al, 2016 ), and ECS ( Vuylsteke and Langhe, 1985 ; Sági et al, 1995 ; Cote et al, 1996 , 2000 ). Bananas are typically genetically transformed using particle bombardment or Agrobacterium -mediated transformation ( May et al, 1995 ; Sági et al, 1995 ).…”
Section: Methods Of Genetic Transformationmentioning
confidence: 99%
“…There is scope to improve more peanut cultivars and other legumes transformation by using these compounds. Measures like explant wounding /micro-injury have been widely followed in transformation studies where some of them have reported a low frequency of transient transformation (116,147). As an alternative to mechanical wounding, sonicationinduced tissue wounding or whisker-mediated transformation can be tried to increase the transformation frequency (113,146).…”
Section: Prospects Regarding Peanut Transformationmentioning
confidence: 99%